Patient-Controlled Real-Time Transcutaneous Electrical Acupoint Stimulation at Neiguan (PC6) for Chemotherapy-Induced Nausea and Vomiting in Breast Cancer: An Exploratory Single-Arm Two-Stage Trial - Huiting Liu; Jie Zhou; Junying Du; Qiongying Shen; Chao Lu; Jianxing Zhang; Weiping Zhang; Ran Ran; Jianqiao Fang; Jiongyao Ye; Hong Gao; Junfan Fang (Current Oncology, 2026)
Chemotherapy-induced nausea and vomiting (CINV) remain difficult to control after discharge despite guideline-based antiemetics. This multicenter exploratory single-arm two-stage trial evaluated patient-controlled, real-time transcutaneous electrical acupoint stimulation (TEAS) at Neiguan (PC6) as an adjunct to standard antiemetic therapy in patients with breast cancer. Forty-eight patients who had experienced CINV and were scheduled at enrollment to receive the same chemotherapy and antiemetic regimens during two consecutive cycles were analyzed. Cycle 1 served as the observation period, and cycle 2 added on-demand wrist-worn TEAS initiated by patients at nausea or vomiting onset during 0–120 h after chemotherapy. Compared with the observation period, TEAS was associated with lower nausea frequency and visual analogue scale scores on days 1–5 and higher nausea response rates on days 1–4. Vomiting frequency and severity were lower on days 1–3, but between-period differences were not significant on days 4–5. SF-36 scores increased and SAS/SDS scores decreased on day 5. Two transient local numbness events occurred, with no serious TEAS-related adverse events. These findings suggest that patient-controlled TEAS is feasible and warrants confirmation in randomized sham-controlled trials.